REVIEW ABOUT RADIOPHARMACEUTICALS: PREPARATION, RADIOACTIVITY, AND APPLICATIONS - ALSHAREF, SHOMOKH; ALANAZI, MASHAEL; ALHARTHI, FATIMAH; QANDIL, DANA; QUSHAWY, MONA (International Journal of Applied Pharmaceutics, 2020)
In the recent few decades, there was a growth in the field of radioactive medicinal agents called radiopharmaceuticals. Radiopharmaceuticals are consisting of radioactive materials called radioisotopes. Radiopharmaceuticals were recently used in both therapeutic and diagnostic purposes. More than 100 radioactive substances are used in nuclear medicine. According to the decay of radioactive substances, there are three types of radioactive decays, alpha particles, beta particles, and gamma radiations. Alpha particles consist of two protons and two neutrons with large mass and charge so it has no penetration power into the skin and has a destructive effect. Beta particles have less charge and less mass so, they can penetrate the tissue and have a less destructive effect than alpha particles and can be used in therapy. Gamma radiations have no mass or charge so they can penetrate the deep tissue of organs so used in diagnosis by imaging using a gamma camera. The radiopharmaceuticals were established in the diagnostic purpose and treatment of several diseases as thyroid gland cancer, hyperthyroidism, bone pain metastasis, kidney dysfunction, and myocardial and cerebral perfusion. The radioactive substance can also be used in the sterilization of thermo-labile substances as syringes, catheters, vitamins, hormones, and surgical dressing. The field of nuclear medicine has several advantages as localization of tumors, safe diagnosis, no accumulation of radiation, and high therapeutic efficacy. Nowadays, the branch of nuclear pharmacy is directed to introduce new radioactive pharmaceutical agents which will be important and effective in the treatment of cancer. The growth in the field of radiopharmaceuticals is important to help millions of patients suffering from tumors all over the world. The data of this review were collected by searching in Google Scholar and PubMed using the following keywords.